2019
DOI: 10.1093/tas/txz169
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of pork carcass weight and leanness parameters in the Ontario commercial pork industry

Abstract: This study aimed to examine the correlation of carcass weight, fat depth, muscle depth, and predicted lean yield in commercial pigs. Data were collected on 850,819 pork carcasses from the same pork processing facility between October 2017 and September 2018. Hot carcass weight was reported following slaughter as a head-on weight; while fat and muscle depth were measured with a Destron PG-100 probe and used for the calculation of predicted lean yield based on the Canadian Lean Yield (CLY) equation [CLY (%) = 68… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
(52 reference statements)
1
3
1
Order By: Relevance
“…In a bivariate analysis, we did for the traits investigated in the present study, a strong negative genetic correlation was observed between FD and LMP (−0.96) and a moderate positive genetic correlation was found between MD and LMP (0.66). These results are consistent with Barducci et al (2019) that found the genetic correlation of −0.96 between FD and predicted lean yield and of 0.41 between MD and predicted lean yield. With positive genetic correlation between MD and LMP, it would have been expected to find some common genes controlling these two traits.…”
Section: Discussionsupporting
confidence: 93%
“…In a bivariate analysis, we did for the traits investigated in the present study, a strong negative genetic correlation was observed between FD and LMP (−0.96) and a moderate positive genetic correlation was found between MD and LMP (0.66). These results are consistent with Barducci et al (2019) that found the genetic correlation of −0.96 between FD and predicted lean yield and of 0.41 between MD and predicted lean yield. With positive genetic correlation between MD and LMP, it would have been expected to find some common genes controlling these two traits.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, the dressing percentage, expressed as a ratio of live weight, and backfat thickness are considered in the production of high-quality livestock products. In a previous study, hot carcass weight was positively correlated with fat and muscle thickness, as well as negatively correlated with lean yield [26]. Although the increased hot carcass weight did not lead to an increase in backfat thickness in our study, the increased hot carcass weight in the ISe group may be related to bone and/or skeletal muscle development.…”
Section: Carcass Characteristics and Proximate Composition Of Pork Loincontrasting
confidence: 57%
“…This increase is driven by both the dilution of fixed production cost over more weight per pig and the improvement of genetic selection of lean-type pigs [ 4 ]. Several studies evaluated the effects of greater slaughter weights on profitability, carcass quality, primal cuts yield, and pork quality (e.g., [ 5 , 6 , 7 , 8 , 9 , 10 ]); however, only in a few studies the slaughter weight considerably exceeded 125 kg [ 5 , 10 ]. This framework results in a pronounced lack of knowledge concerning the quality of the fresh meat of heavy pigs, and in particular on how pork quality of this productive category may be affected by pre-slaughter stressors under conventional conditions.…”
Section: Introductionmentioning
confidence: 99%